Leadership Behavior of Administrators and Supervision within Schools under the Pattani Primary Educational Service Area Office 2 - Puchoh, Larini; Kao-ian , Jarunee; Suwanno , Phimpawee (Al-HIKMAH Journal, 2024)
The purposes of this research is to study the level of leadership behavior of school administrators, to study the level of supervision within schools, to compare leadership behavior of school administrators classified by gender, educational background, work experience and the size of the school, to compare supervision within schools classified by gender, educational background, work experience and the size of the school, to study the relationship between leadership behaviors of administrators and supervision within schools, to process suggestions on leadership behavior of administrators and supervision within schools. The sample group used in this research were school administrators and teachers under the Pattani Primary Educational Service Area Office 2, academic year 2022 for 336 people. The tools used in this research are questionnaire divided into 4 parts. Statistics used in data analysis consisted of frequency, percentage, mean, standard deviation, Pearson’s correlation coefficient, T-test, and F-test. The results show that: First, Leadership behavior of school administrators, the overall was at a high level and Second, Comparison of leadership behavior of school administrators Classified by variable Gender Education level Work experience and size of educational institution, it was found that gender, work experience and size of educational institution They were significantly different at the .05 level, except that the educational levels were not different. Lastly, Suggestions on leadership behavior of administrators and supervision within schools under the Pattani Primary Educational Service Area Office 2, namely, administrators should experiment with new ideas in the work of teachers and there is an opportunity for the community to participate in management Should have an interest in new subjects to develop oneself continuously and regularly.